2001
DOI: 10.1063/1.1334374
|View full text |Cite
|
Sign up to set email alerts
|

Nonperiodic flux to voltage conversion of series arrays of dc superconducting quantum interference devices

Abstract: A theoretical study on the voltage response function V of a series array of dc SQUIDs is presented in which the elementary dc SQUID loops vary in size and, possibly, in orientation. Such series arrays of two-junction SQUIDs possess voltage response functions vs. external magnetic field B that differ substantially from those of corresponding regular series arrays with identical loop-areas, while maintaining a large voltage swing as well as a low noise level. Applications include the design of current amplifiers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Recently, Superconducting Quantum Interference Filters (SQIFs) have been proposed as high resolution magnetometers [8], [9]. SQIFs are arrays of Josephson junctions (JJs) with a specially selected distribution of the loop areas, such that the magnetic field dependent voltage response is a delta-like dip in the vicinity of zero magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Superconducting Quantum Interference Filters (SQIFs) have been proposed as high resolution magnetometers [8], [9]. SQIFs are arrays of Josephson junctions (JJs) with a specially selected distribution of the loop areas, such that the magnetic field dependent voltage response is a delta-like dip in the vicinity of zero magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances that led to nano-SQUIDs makes possible the fabrication of SQUID metamaterials at the nanoscale 27 . The use of SQUID arrays in dc current sensors 28 , filters 29,30 , magnetometers 31 , amplifiers [32][33][34] , radiation detectors 35 , flux-to-voltage converters 36 , as well as in rapid single flux quantum (RFSQ) electronics 37 , has been suggested and realized in the past. However, in most of these works the SQUIDs in the arrays were actually directly coupled through conducting paths.…”
Section: Introductionmentioning
confidence: 99%
“…5 demonstrates that the maximum voltage response ( ) can increase due to the coupling parameter . Previous work has shown that the dynamic range can increase due to the number of loops in a series [1], [2]. The work in this paper demonstrates that by increasing the inductive coupling between the neighboring loops we can also achieve an increase in dynamic range.…”
Section: Resultsmentioning
confidence: 58%
“…4. The dynamic range of a typical SQUID array device with 50 loops is times (or 17 dB) larger than for a conventional single loop SQUID [1], [2]. Hence, increasing the number of element in an the array of SQUIDs increasing the dynamic range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation